Efektifitas Aromaterapi Jahe Terhadap Mual dan Muntah Pada Ibu Hamil di Ruang Kreativa RS Universitas Sebelas Maret - Jujuk Endarwati Eka Wardani; Sulastri Sulastri (Jurnal Ners, 2025)
Pregnancy can affect the mother's body and can cause discomfort during pregnancy, one of which is nausea and vomiting (emesis gravidarum). Treatment that can be given to pregnant women who experience emesis gravidarum apart from pharmacological therapy is non-pharmacological therapy by administering ginger aromatherapy. The aim of this research was to determine the effectiveness of ginger aromatherapy against nausea and vomiting in pregnant women in the culture room at Sebelas Maret University Hospital. This research design uses a case study approach (case report). The data sources for this research were obtained through the process of interviews, observations, and documentation studies regarding nausea and vomiting in pregnant women. Nausea and vomiting were measured before and after the intervention using the Pregnant Unique Quantification of Emesis and Nausea (PUQE) questionnaire. The results of this research on treatment by providing ginger aromatherapy and can be applied to pregnant women who experience nausea and vomiting problems are as expected, the nausea and vomiting decreases with the PUQE value decreasing. The conclusion from this research is that the problem of nausea and vomiting in pregnant women can be resolved by providing ginger aromatherapy and the results are as expected. Ginger aromatherapy can reduce nausea and vomiting in pregnant women in the Culture Room at Sebelas Maret University Hospital.